Improving Knowledge of FMD Outbreak Prevention on Livestock Based on DIMES in Ketawang Village - Mochammad Ilyas Junjunan; Ayu Nurqinasih; Putri Aprilia Afinda; Fajri Parikesit; Alya Zulfana; Venna Narulita Rizqi; M. Maulana Asegaf (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Most of the residents in Ketawang village have side jobs as stock farmers. The population of breeders is 254 people with the number of livestock as many as 489 cows. This service activity is carried out with the aim. Of increasing the knowledge of farmers in Ketawang village regarding the FMD outbreak. This service activity was chosen to broaden the public's knowledge about preventing and handling FMD in their livestock. DIMES (discussion, mediation, and socialization) was then chosen as a problem-solving step because it was considered appropriate to involve active participation from the village because it involved the village's problems and affected the income sources of the villagers. The stages carried out in this service activity consist of (1) Preparation of socialization needs, (2) Implementation of the results of training and mentoring programs, (3) Monitoring and evaluation, (4) Outcomes, and (5) Schedule of activities. Results of this service activity have proven to be useful in increasing knowledge related to FMD. Implementation of monitoring shows that stock farmers respond positively by spraying disinfectants according to what has been taught. Implementation of the evaluation proved that many residents were satisfied with the course of this activity.